MENANAMKAN MINAT LITERASI (BACA TULIS) SEJAK DINI DI SDN NAGACIPTA 02 - Rahmadani Al-Fath, Aulia Suci; Lubis, Rabiyannur; Irham, Irham (An-Nizam, 2024)
Lack of facilities and infrastructure that can support students’ reading activities, as well as lack of support and motivation for students. In the teaching and learning process, teachers also have not implemented innovative and interesting teaching, especially in teaching reading to students from the lower grades, resulting in a lack of interest and interest among students in literacy activities. The purpose of this writing is to explain the importance of literacy in the quality of human resources who are able to compete and keep up with current developments. The implementation method applied was socialization to students at SDN Nagacipta 02 with the theme of instilling an interest in literacy (reading and writing) from an early age, using the flashcards method for reading practice. This activity was held at SDN Nagacipta 02 which is located in Nagacipta Village, Serang Baru District on February 27 2024. The results of this program can be seen in the increased interest of students in reading. When running the program in class 2 and class 4, students appear to be able to participate in the learning process with enthusiasm and full of activity, this can be seen when running the program in class 2 using the flashcards method and for class 4 students it can also foster a sense of cooperation between classmates. Through group work in creative activities to decorate literacy trees. Because motivation and support both in terms of facilities and infrastructure, as well as the ability to package innovative teaching and learning processes can have a big impact on the growth of students’ interest in the learning process, which will influence the achievement of learning goals.